Different combinations of nitrogen and carbon sources influence the growth and postbiotic metabolite characteristics of Lactiplantibacillus plantarum strains isolated from Malaysian foods - Zheng, Qinri; Chia, Suet Lin; Saad, Norazalina; Song, Adelene Ai-Lian; Loh, Teck Chwen; Foo, Hooi Ling (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Postbiotic metabolites produced by Lactiplantibacillus plantarum strains isolated from Malaysian food have been extensively reported for their positive effects on health. Understanding the effects of different combinations of carbon and nitrogen sources on the growth and corresponding characteristics of postbiotic metabolites produced by different strains of L. plantarum is important for various applications. Hence, the effects of different combinations of carbon (glucose, lactose, sucrose and dextrose) and nitrogen (X-SEED Kat, X-SEED Peptone, X-SEED Nucleo Advanced, Nucel875 MG, FM888 and FM902) sources on the growth of six strains of L. plantarum (RG11, RG14, RI11, RS5, TL1 and UL4) and the functional characteristics (bacteriocin inhibitory activity, antioxidant activity and lactic acid concentration) of their respective postbiotic metabolites were investigated in this study. UL4 produced the highest viable cell population with sucrose and Nucel875 nitrogen source. The UL4 strain also produced the strongest bacteriocin inhibitory activity with dextrose and FM888 nitrogen source. In comparison, the RI11 strain produced the highest lactic acid concentration with dextrose and Nucel875 nitrogen source and the highest reducing power of RS5 and TL1 postbiotic metabolites was achieved with MRS medium. In the combination of sucrose and X-Seed KAT nitrogen source, RG14 produce the highest hydroxyl radical scavenging activity. The effects of different combinations of carbon and nitrogen sources on the viable cell population of L. plantarum strains and the respective functional characteristics of postbiotic metabolites were strain dependent. The current study also revealed that fermentation media were an important factor that greatly impacted the functionalities of postbiotic metabolites due to the presence of various bioactive compounds that contributed to high antioxidant and antimicrobial properties. The results of this study will facilitate the subsequent medium design and optimisation for the development and production of specific postbiotic metabolites produced by the respective L. plantarum strain for their applications in various industries.